Self-Care Practices for Common Colds by Primary Care Patients: Study Protocol of a European Multicenter Survey—The COCO Study. (2nd September 2015) - Weltermann, Birgitta M.; Gerasimovska-Kitanovska, Biljana; Thielmann, Anika; Chambe, Juliette; Lingner, Heidrun; Pirrotta, Enzo; Buczkowski, Krzysztof; Tekiner, Selda; Czachowski, Slawomir; Edirne, Tamer; Zielinski, Andrzej; Yikilkan, Hülya; et al.
Abstract : Background. Self-care for common colds is frequent, yet little is known about the spectrum, regional differences, and potential risks of self-care practices in patients from various European regions. Methods/Design. We describe the study protocol for a cross-sectional survey in 27 primary care centers from 14 European countries. At all sites, 120 consecutive adult patients, who visit their general practitioner for any reason, filled in a self-administered 27-item questionnaire. This addresses patients' self-care practices for common colds. Separately, the subjective level of discomfort when having a common cold, knowing about the diseases' self-limited nature, and medical and sociodemographic data are requested. Additionally, physicians are surveyed on their use of and recommendations for self-care practices. We are interested in investigating which self-care practices for common colds are used, whether the number of self-care practices used is influenced by knowledge about the self-limited nature of the disease, and the subjective level of discomfort when having a cold and to identify potential adverse interactions with chronic physician-prescribed medications. Further factors that will be considered are, for example, demographic characteristics, chronic conditions, and sources of information for self-care practices. All descriptive and analytical statistics will be performed on the pooled dataset and stratified by country and site. Discussion. To our knowledge, COCO is the first European survey on the use of self-care practices for common colds. The study will provide new insight into patients' and general practitioners' self-care measures for common colds across Europe.